Bid Regulations in a Multi-unit Uniform Price Auction - Anette Boom (Copenhagen Business School (CBS), Department of Economics, 2016)
This paper examines the effect of bid regulations on the range of potential equilibrium prices in a multi-unit uniform price auction with heterogenous bidders. General bid caps destroy equilibria with prices above the bid cap and create new equilibria with prices way below the cap. A cap only for larger firms does not guarantee market prices below that cap. A sufficiently high bid floor only for smaller firms destroys some or all pure strategy equilibria despite their prices being above the bid floor. With a general bid floor this happens only with considerably higher bid floors.
hdl:10398/9409
Keywords: D43; D44; L12; L13; L51; 330; Multi-unit Auctions; Heterogenous Bidders; Bid Regulation